Furies in beeld. Herinneringen aan gewelddadige innames van steden tijdens de Nederlandse Opstand op zeventiende-eeuwse schilderijen - Eekhout, Marianne (De Zeventiende Eeuw: Cultuur in de Nederlanden in interdisciplinair perspectief, 2014)
From different levels in the urban community artists received commissions to paint violent scenes such as the looting and pillaging of cities (sacks). Individuals hung such paintings on the walls of their homes to remember what the city had gone through. Magistrates sometimes also commissioned artists to depict violence on paintings for the town hall. The paintings were inspired by existing prints made by Frans Hogenberg. These works became a subgenre of paintings which combined a city view with the depiction of violence. They show that even the non-glorious past could be remembered within the urban community and added to the integration of the Dutch Revolt into a city’s history.